Analysis of Factors Affecting the Skills of Nurses in Installation of Infuses at Mitra Medika Amplas Hospital - Nurlaila Qodrianti Siregar; Arifah Devi Fitriani; Asriwati Amirah (Newinera Publisher, 2020)
Nurses are one of the most decisive factors in achieving optimal health services with quality nursing care. The quality of good health services can be seen from the facilities, technology, physical appearance, and behaviour of employees which must reflect high professionalism and commitment. Patient complaints related to the infusion by nurses at Mitra Medika Amplas Hospital are still common. The research objective was to analyze the factors affecting the skills of nurses in the infusion set up at Mitra Medika Hospital Amplas. The research design used an analytic survey with a cross-sectional design. The study population of all nurses who work in outpatient and inpatient rooms were 190 people. The sampling technique used cluster random sampling. The number of samples to be studied was 100 respondents. Data analysis was performed by univariate, bivariate, and multivariate analyses. The results of the research variable knowledge obtained p-value = .04, attitude 1.0, leadership .53, work design structure .209, experience .166, and 1.0 career path. The p-value of knowledge <.05 means that the influence between knowledge and skills of nurses in infusion found. The variable attitude, leadership, work design structure, experience, and career path p-value >.05 means the influence between the knowledge and skills of nurses in infusion not found. Based on 6 variables tested, only the knowledge factor that had an influence on the skills of nurses in the infusion. It is recommended for health workers to always carry out nursing care based on the applicable SPO, for further researchers it is recommended to examine other factors.